Preterm premature rupture of the membranes: Guidelines for clinical practice from the French College of Gynaecologists and Obstetricians (CNGOF). (May 2019) - Schmitz, Thomas; Sentilhes, Loïc; Lorthe, Elsa; Gallot, Denis; Madar, Hugo; Doret-Dion, Muriel; Beucher, Gaël; Charlier, Caroline; Cazanave, Charles; Delorme, Pierre; Garabédian, Charles; Azria, Elie; et al.
Abstract: In France, the frequency of premature rupture of the membranes (PROM) is 2%–3% before 37 weeks' gestation (level of evidence [LE] 2) and less than 1% before 34 weeks (LE2). Preterm delivery and intrauterine infection are the major complications of preterm PROM (PPROM) (LE2). Prolongation of the latency period is beneficial (LE2). Compared with other causes of preterm delivery, PPROM is associated with a clear excess risk of neonatal morbidity and mortality only in cases of intrauterine infection, which is linked to higher rates of in utero fetal death (LE3), early neonatal infection (LE2), and necrotizing enterocolitis (LE2). The diagnosis of PPROM is principally clinical (professional consensus). Tests to detect IGFBP-1 or PAMG-1 are recommended in cases of uncertainty (professional consensus). Hospitalization is recommended for women diagnosed with PPROM (professional consensus). Adequate evidence does not exist to support recommendations for or against initial tocolysis (Grade C). If tocolysis is prescribed, it should not continue longer than 48 h (Grade C). The administration of antenatal corticosteroids is recommended for fetuses with a gestational age less than 34 weeks (Grade A) and magnesium sulfate if delivery is imminent before 32 weeks (Grade A). The prescription of antibiotic prophylaxis at admission is recommended (Grade A) to reduce neonatal and maternal morbidity (LE1). Amoxicillin, third-generation cephalosporins, and erythromycin (professional consensus) can each be used individually or eythromycin and amoxicillin can be combined (professional consensus) for a period of 7 days (Grade C). Nonetheless, it is acceptable to stop antibiotic prophylaxis when the initial vaginal sample is negative (professional consensus). The following are not recommended for antibiotic prophylaxis: amoxicillin-clavulanic acid (professional consensus), aminoglycosides, glycopeptides, first- or second-generation cephalosporins, clindamycin, or metronidazole (professional consensus). Women who are clinically stable after at least 48 h of hospital monitoring can be managed at home (professional consensus). Monitoring should include checking for clinical and laboratory factors suggestive of intrauterine infection (professional consensus). No guidelines can be issued about the frequency of this monitoring (professional consensus). Adequate evidence does not exist to support a recommendation for or against the routine initiation of antibiotic therapy when the monitoring of an asymptomatic woman produces a single isolated positive result (e.g., elevated CRP, or hyperleukocytosis, or a positive vaginal sample) (professional consensus). In cases of intrauterine infection, the immediate intravenous administration (Grade B) of antibiotic therapy combining a beta-lactam with an aminoglycoside (Grade B) and early delivery of the child are both recommended (Grade A). Cesarean delivery of women with intrauterine infections is reserved for the standard obstetric indications (professional consensus). Expectant management is recommended for uncomplicated PROM before 37 weeks (Grade A), even when a sample is positive for Streptococcus B, as long as antibiotic prophylaxis begins at admission (professional consensus). Oxytocin and prostaglandins are two possible options for the induction of labor in women with PPROM (professional consensus).